Digital platforms like Airbnb stimulate the local economy in rural areas of France for the year 2023 - Ayaichia zaara; Daghrir fathi (المجلة الدولية للأداء الاقتصادي)
The research paper examines the economic impact of short-term rentals in rural France via platforms like Airbnb in 2023. Through the analysis of available statistics, it was found that these platforms have contributed to the flourishing of rural areas in France due to their effective strategies and support and funding programs that have benefited French rural regions, leading to positive economic growth for French rural communities.